Views of wheelchair users and caregivers regarding a passive safety monitoring system for electric powered wheelchair operators with cognitive impairment. Issue 1 (2nd January 2022) - Kearns, William D.; Becker, Adam J.; Condon, John P.; Molinari, Victor; Hanson, Ardis; Conover, William; Fozard, James L.
ABSTRACT: The opinions of cognitively intact current wheelchair users and their professional caregivers were solicited to explore acceptability of the concept of a passive electric wheelchair-mounted movement monitor to track driving safety and cognitive impairment. Two focus groups of electric wheelchair users (N = 9), and two focus groups of staff caregivers (N = 8) were conducted at a congregate care facility. Participants also completed a questionnaire examining their perceptions of the concept. The results indicated most wheelchair users and staff caregivers were receptive to the idea of a passive safety monitoring system for wheelchairs to detect cognitive impairment. Three main and interrelated themes emerged regarding how the device could promote safety, how such a system might infringe upon the users' autonomy, and how and to whom the cognitive state information should be communicated. Legal, training, and marketing issues reflected similar concerns over balancing autonomy with safety issues. If successfully addressed, it appears there would be support for the device's use not only for older adults in institutional settings, but perhaps also among community living younger and older adults. A passive safety monitoring system for wheelchairs is acceptable to wheelchair users and can be successfully marketed if developers balance autonomy and safety concerns.